LAPORAN KETERANGAN PERTANGGUNGJAWABAN KEPALA DAERAH TERHADAP HASIL PENYELENGGARAAN URUSAN PEMERINTAHAN DALAM PERSPEKTIF OTONOMI DAERAH - Mubaraq Mubaraq; Tri Widiastuti, Arga Chon Feriandref, Eka Ermala, Othman Ballan, Duwi Aryadi (JOURNAL OF LAW AND NATION, 2024)
This study aims: 1) to find out how the mechanism of the accountability report on the District Head as impact the result of government’s affairs administration according to District Government’s statute. 2) to know and analyze the implication of the accountability report on the District Head as impact the result of government’s affairs administration has been appropriated by the principle of autonomous district. With that aim then the discussed issues are: 1) how the mechanism of the accountability report on the District Head impact the result of government’s affairs administration according to District Government’s statute?2) is implication of the accountability report on the District Head impact the result of government’s affairs administration has been appropriated by the principle of autonomous district? By the formulation of that problem then the research methods is using normative juridical research with statute approach, historical approach, conceptual approach and political approach. The legal materials that collected are: primary legal materials, secondary legal materials, and tertiary legal materials. Analysis of the collected legal materials is carried out by inventoring, systematizationing, and interpreting. The results showed that: 1) The Mechanism of the accountability report on the District Head just have the quality of Formalistic Administrative, so if it linked with accountability’s concept is not become things that accountable as a law accountability, political accountability, and administration accountability. 2) there is no implication from the accountability report on the District Head as a responsible person in every District Government’s administration policy, then the implication from the accountability report on the District Head has not reflecting what is known in autonomous district principle according to autonomous district’s statute that is tangible, comprehensive and responsible. Recommendation: the statute number 23year 2014 should be include the sanction of the accountability report on the District Head, so in that report has found a mismatch of the substantable and tangible in peoples then it should be followed up properly in law, administrative, and politic.